Globalization of Behavioral Risks Needs Faster Diffusion of Interventions - Shahul Ebrahim, MD, MSc, PhD; Joxel Garcia, MD, MBA; Achmed Sujudi, MS, MBA; Hani Atrash, MD, MPH (Centers for Disease Control and Prevention, 2007)
International trade, population migration, changes in living conditions (i.e., consumption transition, nutritional transition), and changes in production, marketing, and availability of consumer goods (i.e., production transition) have brought about continuous and rapid changes in the human environment. Such changes have improved the health and economic status of many people in developing countries. At the same time, a parallel phenomenon is occurring: the rapid emergence and expansion of modifiable risk behaviors. These behaviors adversely affect the national health of developing countries and that of future generations because of their impact on maternal, child, and adolescent health. Furthermore, these behaviors are increasing at a faster rate than interventions to curb their growth are being implemented. We discuss the current status of five modifiable risk behaviors - alcohol consumption, tobacco use, overweight and obesity, low fruit and vegetable consumption, and physical inactivity - to emphasize the need for global advocacy and local action to enhance policy formulation and diffusion of interventions necessary to moderate the spread of these behaviors.